Positivism Theory in the Context of Modern Legal Thought - Donny Widianto; Zainal Arifin Hoesein (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The theory of legal positivism plays a crucial role in the development of modern legal thought by emphasizing the importance of written and systematic norms in law enforcement. This approach is based on the assumption that the law is the product of regulations made by state institutions, as stipulated in various laws, including the 1945 Constitution, the Criminal Code (KUHP), and Law Number 12 of 2011 concerning the Establishment of Laws and Regulations. The methodology used in this study is qualitative analysis through literature studies and interviews with legal experts to explore the understanding of the application of positivism theory in legal practice in Indonesia. The results show that although positivism provides a strong framework for legal analysis and supports legal certainty, there are still significant challenges related to the application of the values of justice and morality in the legal system. This study concludes that to achieve social justice, there needs to be an integration between positivism and moral principles in modern legal practice.